Dysautonomic responses during percutaneous carotid intervention. Issue 2 (30th August 2014) - Bujak, Marcin; Stilp, Erik; Meller, Stephanie M.; Cal, Nicolas; Litsky, Jason; Setaro, John F.; Mena, Carlos
<x xml:space="preserve">Abstract</x> Percutaneous carotid artery stenting (CAS) has emerged as a less invasive alternative to carotid endarterectomy for the treatment of carotid atherosclerotic disease. The main risk of CAS is the occurrence of neuro‐vascular complications; however, carotid artery stenting‐related dysautonomia (CAS‐D) (hypertension, hypotension, and bradycardia) is the most frequently reported problem occurring in the periprocedural period. Alterations in autonomic homeostasis result from baroreceptor stimulation, which occurs particularly at the time of balloon inflation in the region of the carotid sinus. The response can be profound enough to induce asystole or even complete cessation of postganglionic sympathetic nerve activity. Frequency and factors predisposing a patient to CAS‐D have been investigated in several studies; however, there are significant discrepancies in results among reports. Lack of consistent findings may arise from using different methods and definitions, as well as other factors discussed in detail in this review. Furthermore, a correlation of CAS‐D with short and long‐term outcomes has been investigated only in small and mostly retrospective studies, explaining why its prognostic significance remains uncertain. In this manuscript, we have focused on risk factors, pathophysiology and management of periprocedural autonomic dysfunction. As there is no standardized approach to the treatment of CAS‐D, we present an algorithm for the periprocedural management of patients undergoing CAS. The proposed algorithm was developed based on our procedural experience as well as data from the available literature. The Yale Algorithm was successfully implemented at our institution and we are currently collecting data for short‐ and long‐term safety. © 2014 Wiley Periodicals, Inc.